PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM KONTRAK BAKU PERJANJIAN PEMBIAYAAN KONSUMEN DI PT. WOM FINANCE PEKANBARU DITINJAU DARI UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Septian Bestari S; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The agreement basically an agreement between two parties to obtain a desired result. As in reaching the agreement there are various phases of their stage of negotiations until the deal . This makes the parties are free to enter into an agreement with anyone in accordance with the principle of freedom of contract is in the law of contract . In the agreement, there are also clauses that constitute the content of the agreement clauses which were the result of agreements between the parties . The consumer finance company PT . WOM Finance Pekanbaru , agreements are called standard contract (standard contract). This agreement contains clauses that have been made by PT . WOM Finance or so-called raw klasula . It is certainly aggravating the other party , namely the consumer , because the consumer does not participate in the making the formulation , so that the need for consumer protection . Consumer protection is regulated in Law No. 8 of 1999 on Consumer Protection .In this study , the authors establish the following principal issue , as to whether the standard clause in the agreement in accordance with the arrangements inclusion of standard clauses in the Consumer Protection Act ? What is the legal effect of the inclusion of standard clauses in consumer financing agreement ? and how remedies that can be taken by the Customer to the agreement.Writing is when viewed from the type of research that is classified as a sociological research that studies looking at the correlation between the law with the public , so as to reveal the effectiveness of the rule of law in society , whereas if seen from the nature of this research is descriptive research that explains in clear sentences form and detailed.From the results of research conducted , the consumer finance agreements are standard clauses which are not in accordance with the arrangement of the inclusion of standard clauses set out in Article 18 paragraph ( 1 ) letter of Undang-Undang Nomor 8 Tahun 1999 Tentang Perlindungan Konsumen. It is also contrary to the terms of the agreement because the validity of halal , which is contrary to the principles of morality , public order principles , and other legislation . So also with the layout and writing the standard clause is too small that it is difficult to be seen clearly by the consumer , and is also contrary to Article 18 paragraph ( 2 ) of Undang-Undang Perlindungan Konsumen . With the clauses in consumer financing agreement as opposed to setting the inclusion of standard clauses , and the location and form of writing that is contrary to the Undang-Undang Perlindungan Konsumen , we can conclude the agreement null and void . Therefore, if there is a dispute between the consumer and the company , consumers can take legal actions are filed to the Consumer Dispute Settlement Board ( Non-Litigation ) and also to the District Court ( Litigation ) .Keywords : Consumer Protection - Agreements - Standard Clauses